The Combination of Ant Colony Optimization (ACO) and Tabu Search (TS) Algorithm to Solve the Traveling Salesman Problem (TSP) - Dewantoro, Rico Wijaya; Sihombing, Poltak; Sutarman (2019 3rd International Conference on Electrical, Telecommunication and Computer Engineering (ELTICOM), 2019)
In this research, the authors want to propose the combination of Ant Colony Optimization Algorithm and Tabu Search Algorithm as local search to solve Traveling Salesman Problem. This is a hybrid method of ACO to find best routes and get a better running time. One of the classic problems that can be used is TSP. In this research, the authors will compare the hybrid of ACO-TS and ACO. In this research, the hybrid of ACO-TS got the best routes and a better running time than ACO itself. It means that combination of ACO-TS is better than ACO itself. Therefore to get the best routes and a better running time, the author suggested the ACO-TS algorithm to solve TSP.